1960
DOI: 10.1139/y60-004
|View full text |Cite
|
Sign up to set email alerts
|

The Selective Proteolytic Enzyme Inhibitory Action of Benzethonium Chloride

Abstract: Acute hemorrhagic pancreatitis in humans is thought to be perpetuated by the autolytic processes catalyzed by trypsin and lipase. This study is an integral part of our search for trypsin and lipase inhibitors to be used in the treatment of this disease.Benzethonium chloride was found to inhibit tryptic activity in vitro. The proteolytic activity of rabbit's serum was inhibited, and the inhibition was most pronounced 6 to 12 hours after the subcutaneous injection of the compound. Fibrinolysin was also inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1962
1962
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The quaternary ammonium compound benzethonium chloride (benzyldimethyl(2-[2+-1,1,3,3_tetramethylbutylphenoxy)ethoxy] -ethyl) ammonium chloride) (Mann Research Laboratories, Inc., New York, USA) has been reported among other compounds to inhibit trypsin action [l] . This has been later confirmed in studies in which benzethonium chloride was also found to inhibit the proteolytic activity of rabbit serum [2]. Fibrinolysin was also inhibited but the compound had no inhibiting effect on the action of chymotrypsin, pepsin, or lipase.…”
mentioning
confidence: 67%
“…The quaternary ammonium compound benzethonium chloride (benzyldimethyl(2-[2+-1,1,3,3_tetramethylbutylphenoxy)ethoxy] -ethyl) ammonium chloride) (Mann Research Laboratories, Inc., New York, USA) has been reported among other compounds to inhibit trypsin action [l] . This has been later confirmed in studies in which benzethonium chloride was also found to inhibit the proteolytic activity of rabbit serum [2]. Fibrinolysin was also inhibited but the compound had no inhibiting effect on the action of chymotrypsin, pepsin, or lipase.…”
mentioning
confidence: 67%
“…. Therefore, the crystallographic planes are maintained in solution and in the presence of glycerol are a strong indication for i) a periodicity in the solution phase that is dependent on the nature and possibly charge of the anion, ii) the preservation of similar lengths scales corresponding to short distances between charged groups that had the same sign but independent of the nature of the anion and iii) the absence of ionic groups of opposite charge but with a spacing at a distance which can be considered periodic which are dependent on the nature and charge of the anions and iv) the differences in biological activities 4,7,[12][13][14][15][16][17] can be explained inter alia on the basis of differences in balances of polar parts of the anions that are separated by unique distances that are similar to the separation between apolar parts of the Bzth-skeleton. At particular distances from the polar groups e.g.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Noteworthy, is also the inhibition of proteases by Bzth-Cl at ∼0.1 mM Bzth-Cl and similarly for the HIV protease. 7 The reported biological activities account for Bzth-Cl concentrations in the µM range, that are much lower than the critical micelle concertation (CMC) of Bzth-Cl of 0.54 mM and 1.84 mM as determined recently by intrinsic fluorescence spectroscopy in water, 8 or of 0.84 mM to 1.15 mM in 0.01 M Tris-HCl buffer, pH 7.5 (293 K) determined by light scattering, surface tension and electric conductivity measurements. [9][10][11] The inhibition of the acetylcholinesterase and the cholinesterase, respectively, is completely inhibited at K i ∼ 0.15 mM.…”
Section: Introductionmentioning
confidence: 99%